Prevention of the Sexual Abuse of Children in the School Environment - Krzysztof Biel (Ignatianum University Press, 2021)
The aim of the article is to present the assumptions of the prevention of sexual violence against children in the school environment. Child sexual abuse has become a global problem that affects not only the family environment, but educational institutions as well. One example of such an institution is a school where, under the guise of upbringing, there may be numerous abuses committed by people who are an authority in the child's life. School staff members are often unaware of institutional grooming and its perpetrators, which means that the entire institution may unknowingly contribute to promoting child sexual abuse. The author first presents the methods of grooming used by perpetrators, pointing to activities aimed at children and the mechanisms of institutional grooming that may create a specific culture that makes it difficult to protect children. The author then presents the standards and strategies for prevention in schools, paying attention to the need to involve the entire community: conducting proper recruitment and training of employees and constructing preventive programs adapted to the age and development of children and their proper implementation.